Anatomy of the Great Posterior Radiculomedullary Artery - Perez Perez, V.H. (AJNR Am J Neuroradiol, 2019)
BACKGROUND AND PURPOSE: Although considerable variability exists as to the overall caliber of radiculomedullary arteries, dominant radiculomedullary arteries such as the artery of Adamkiewicz exist. The existence of a great posterior radiculomedullary artery has attracted little attention and has been a matter of debate. The aim of this anatomic study was to determine the presence or absence of the great posterior radiculomedullary artery. MATERIALS AND METHODS: We performed microsurgical dissection on formaldehyde-fixed cadaveric human spinal cords. The artery of Adamkiewicz in the spinal cord specimens (n = 50) was injected with colored latex until the small-caliber arterial vessels were filled and the great posterior radiculomedullary artery was identified. The course, diameter, and location of great posterior radiculomedullary artery were documented. RESULTS: A great posterior radiculomedullary artery was identified in 36 (72%) spinal cord specimens. In 11 (22%) specimens, bilateral great posterior radiculomedullary arteries were present. In 13 cases (26%), a unilateral left-sided great posterior radiculomedullary artery was identified. In 11 cases (22%), a unilateral right-sided great posterior radiculomedullary artery was identified. In 1 specimen (2%), 3 right-sided great posterior radiculomedullary arteries were noted. The average size of the great posterior radiculomedullary arteries was 0.44 mm (range, 0.120–0.678 mm on the left and 0.260–0.635 mm on the right). CONCLUSIONS: A great posterior radiculomedullary artery is present in most (72%) individuals. The authors describe the microsurgical anatomy of the great posterior radiculomedullary artery with emphasis on its morphometric parameters as well as its implications for spinal cord blood supply. Variations of the arterial supply to the dorsal cord are of great importance due to their implications for ischemic events, endovascular procedures, and surgical approaches.